Large Herbivores Affecting Permafrost – Impacts of Grazing on Permafrost Soil Carbon Storage in Northeastern Siberia - Windirsch, Torben; Grosse, Guido; Ulrich, Mathias; Forbes, Bruce C.; Göckede, Mathias; Wolter, Juliane; Macias-Fauria, Marc; Olofsson, Johan; Zimov, Nikita; Strauss, Jens (2021)
The risk of carbon emissions from permafrost ground is linked to ground temperature and thus in particular to thermal insulation by vegetation and organic soil layers in summer and snow cover in winter. This ground insulation is strongly influenced by the presence of large herbivorous animals browsing for food. In this study, we examine the potential impact of large herbivore presence on the ground carbon storage in thermokarst landscapes of northeastern Siberia. Our aim is to understand how intensive animal grazing may affect permafrost thaw and hence organic matter decomposition, leading to different ground carbon storage, which is significant in the active layer. Therefore, we analysed sites with differing large herbivore grazing intensity in the Pleistocene Park near Chersky and measured maximum thaw depth, total organic carbon content and decomposition state by δ 13 C isotope analysis. In addition, we determined sediment grain size composition as well as ice and water content. We found the thaw depth to be shallower and carbon storage to be higher in intensively grazed areas compared to extensively and non-grazed sites in the same thermokarst basin. The intensive grazing presumably leads to a more stable thermal ground regime and thus to increased carbon storage in the thermokarst deposits and active layer. However, the high carbon content found within the upper 20 cm on intensively grazed sites could also indicate higher carbon input rather than reduced decomposition, which requires further studies. We connect our findings to more animal trampling in winter, which causes snow disturbance and cooler winter ground temperatures during the average annual 225 days below freezing. This winter cooling overcompensates ground warming due to the lower insulation associated with shorter heavily grazed vegetation during the average annual 140 thaw days. We conclude that intensive grazing influences the carbon storage capacities of permafrost areas and hence might be an actively manageable instrument to reduce net carbon emission from these sites.